The need for craniofacial trauma and oncologic reconstruction in global surgery - Catherine A. Wu; Rohini Dutta; Sargun Virk; Nobhojit Roy; Kavitha Ranganathan (Elsevier, 2021)
The global burden of surgical disease is concentrated in low- and middle-income countries and primarily consists of injuries and malignancies. While global reconstructive surgery has a long and well-established history, efforts thus far have been focused on addressing congenital anomalies. Craniofacial trauma and oncologic reconstruction are comparatively neglected despite their higher prevalence. This review explores the burden, management, and treatment gaps of craniofacial trauma and head and neck cancer reconstruction in low-resource settings. We also highlight successful alternative treatments used in low-resource settings and pearls that can be learned from these areas.